2018 IEEE International Conference on Communications (ICC) 2018
DOI: 10.1109/icc.2018.8422892
|View full text |Cite
|
Sign up to set email alerts
|

ALOHA-NOMA for Massive Machine-to-Machine IoT Communication

Abstract: This paper proposes a new medium access control (MAC) protocol for Internet of Things (IoT) applications incorporating pure ALOHA with power domain non-orthogonal multiple access (NOMA) in which the number of transmitters are not known as a priori information and estimated with multihypothesis testing. The proposed protocol referred to as ALOHA-NOMA is not only scalable, energy efficient and matched to the low complexity requirements of IoT devices, but it also significantly increases the throughput. Specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 12 publications
(18 reference statements)
0
38
0
2
Order By: Relevance
“…Partindo para a comunicação a múltiplos saltos, o trabalho proposto em [11] estuda o desempenho da taxa de erro de bit (BER, do inglês Bit Error Rate) em uma rede aleatória Aloha. Em trabalhos mais recentes, como os apresentados em [7], [9] e [15], este protocolo também foi utilizado pois ainda possui aplicações práticas válidas por sua menor complexidade, se comparado a outros protocolos MAC mais novos.…”
Section: Trabalhos Relacionadosunclassified
See 1 more Smart Citation
“…Partindo para a comunicação a múltiplos saltos, o trabalho proposto em [11] estuda o desempenho da taxa de erro de bit (BER, do inglês Bit Error Rate) em uma rede aleatória Aloha. Em trabalhos mais recentes, como os apresentados em [7], [9] e [15], este protocolo também foi utilizado pois ainda possui aplicações práticas válidas por sua menor complexidade, se comparado a outros protocolos MAC mais novos.…”
Section: Trabalhos Relacionadosunclassified
“…todo, é importante considerar o protocolo de acesso ao meio (MAC, do inglês Medium Access Control) integrado com o consumo da camada física, assim como também o esquema de roteamento. Aqui, no caso do protocolo MAC, foi considerado o slotted Aloha [8] que, embora apresente baixa vazão, é amplamente utilizado devido a sua baixa complexidade que combinado com outras técnicas de comunicação como NOMA (do inglês Non-Ortoghonal Multiple Access) e SIC (do inglês Successive Interference Cancelation) pode melhorar substancialmente o desempenho de sistemas de comunicação sem fio [7], [9].…”
Section: Introductionunclassified
“…In this work, to obtain the proper power level set, the number of active devices is estimated by the gateway and then based on that the set is determined. In a similar approach, in [20], the estimated number of active devices is broadcasted to the devices, where using this information, each device adjusts its transmission power properly. In [22], the cell area is divided into different layers, where devices in different layers have different target received power.…”
Section: Related Workmentioning
confidence: 99%
“…There are also spreading-based NOMA schemes which utilizes the user-specific low crosscorrelation real/complex-valued spreading sequences to enable non-orthogonal transmissions [10]. To support massive connectivity, many existing papers aim to incorporate code-domain NOMA [12]- [14], or power-domain NOMA [15]- [21] into contention-based random access schemes such as pure ALOHA and slotted ALOHA. In this article, we adopt power-domain NOMA 1 as an enabling technology to enhance the conventional slotted-ALOHA-based RA procedure in NB-IoT and LTE-M, by allowing multiple IoT devices to transmit messages using the same uplink resource [22].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the conventional RA schemes such as pure ALOHA and slotted ALOHA, this newly proposed NOMA-RA scheme is more spectrum-efficient. Focusing on the novel NOMA-RA scheme, some research papers have been published which evaluate the throughput performance, such as [15]- [21]. The combination of pure ALOHA and power-domain NOMA was considered in [15], which showed that the introduction of NOMA results in a higher throughput, compared to the conventional pure ALOHA.…”
Section: Introductionmentioning
confidence: 99%